(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
If the laws are examined collectively, several gaps might be discovered. When examining legislation collectively, it becomes apparent that there are inconsistencies between them in various aspects. The primary motivation for undertaking this work stems from the researcher’s observation of a concerning issue. When the Constitution of India, Criminal Procedure Code, Witness Protection Scheme, 2018, and the Indian Evidence Act are examined collectively, it becomes apparent that the level of protection provided by the State to Hostile Witnesses is not ideal. Although the primary purpose of the Witness Protection Scheme is to safeguard witnesses and discourage them from becoming hostile, the Evidence Act allows for cross-examination of witnesses who have been turned hostile by the party who called them to the stand. While the Constitution of India guarantees the right for citizens to not be compelled to be witnesses against themselves, it does not provide the same level of protection for ordinary witnesses as it does for the accused. Additionally, the CrPC outlines the procedure for police officers to record statements from witnesses during investigations, which can later be used if the witness is declared hostile under the Evidence Act. Upon careful observation, a pressing question emerges: where is the safeguard for an impartial witness? Regardless of the circumstances, the witness’s identity will inevitably come to light. By employing techniques such as cross-examination, a party can uncover the information that the witness is reluctant to divulge. The Constitution of India offers safeguards for the accused through Article 20(3); however, it does not explicitly extend any form of protection to an impartial witness in a case. This is the reason why; initially, no one comes forward as a witness in certain criminal cases, resulting in the acquittal of the accused and ultimately leading to the delivery of injustice. The researchers aim to emphasize this through their work.